Characteristics and Activities of Teachers on Distance Learning Programs that Affect Their Ratings - Stanišić Stojić, Svetlana M.; Dobrijević, Gordana; Stanišić, Nemanja; Stanić, Nenad (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
This paper presents an analysis of teachers’ ratings on distance learning undergraduate study programs: 7,156 students enrolled in traditional and 528 students enrolled in distance learning studies took part in the evaluation questionnaire, assessing 71 teachers. The data were collected from the Moodle platform and from the Singidunum University information system, and then analysed with SPSS statistical software. The parameters considered as potentially affecting teacher ratings are: number of teachers engaged in a particular course, total number of courses in which the teacher is engaged, teacher’s gender and age, total number of the available resources, and so forth. The results imply that scores assigned to individual teachers are consistent in both traditional and distance learning programs. The average rate was perceived to be lower when there were several teachers in a single course; such an effect was enhanced in cases where there was a significant age discrepancy among them. The other factors considered did not show a significant association with teacher ratings. Students’ main remarks about the work of the teachers have been summarised at the end of this paper. Possible explanations and implications of the results are discussed and recommendations are given.